Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Sung-Han Kim; Ju-Wook Baek; Ju-Wook Baek; Hyun-Jeong Jeong; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Jin Young Choi; et al. (Frontiers in Marine Science)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O2 m–2 d–1, and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O2 m–2 d–1. The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m-2 d–1, and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m–2 d–1, and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m–2 d–1 for nitrogen, from 0.02 to 0.05 mmol m–2 d–1 for phosphate, and from 6.72 to 9.11 mmol m–2 d–1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.